TINGKAT KESEHATAN PERBANKAN SYARIAH DAN POTENSI FINANCIAL DISTRESS PADA MASA PANDEMI COVID-19 - Nona Jane Onoyi; Diana Titik Windayati; Nona Jane Onoyi (Pascasarjana Universitas Riau Kepulauan, 2022)
The purpose of this this study is to determine the effect of bank health level in predicting the potential of financial distress during the Covid-19 pandemic.This study uses the bank health level proxied by CAR, NPF, ROA, BOPO and FDR as independent variables. Meanwhile financial distress proxied by Z-Score as dependent variable. The population of study is Islamic Banks listed on Financial Services Authority (OJK) in 2020 as many as 15 banks. The sample of this studytook 12 banks with purpose sampling method. Multiple linear regression method used in this study. The result show that partially CAR, ROA and FDR variables have a significant effect on financial distress, meanwhile NPF and BOPO variables have no significant effect on financial distress. Simultaneously CAR, NPF, ROA, BOPO and FDR variables have a significant effect on financial distress. Suggestion for banks are to maintain health level during the prolonged Covid-19 pandemic. For banks that have entered the prediction of financial distress based on this research, they have to immmediately make change by making efficent use of finance, restructuring and digitizing banking.